THE EFFECT OF TRANSFORMATIONAL LEADEARSHIP, WORK MOTIVATION AND SELF-EFFICACY ON EMPLOYEE PERFORMANCE IN PT MITRA KRIDA MANDIRI, BANDUNG - Cahya Putri Damayanti , Ni Luh Made; Dwi Puspitawati, Ni Made; Putu Purnawati, Ni Luh Gede (Sekolah tinggi ilmu ekonomi pemuda, 2024)
The success and continuity of an organization's activities are greatly influenced by the workforce it has. Labor is one factor that plays an important role in every company. This research aims to determine the influence of transformational leadership, cmotivation, and self-efficacy on employee performance. This research was conducted at PT Mitra Krida Mandiri in Badung Regency. The population and sample in this research are employeePT Mitra Krida Mandiri in Badung Regency which totaled 66 people as research respondents. The method for determining the sample in this research is method saturated sampling. Data collection was carried out through observation, interviews, questionnaire methods, and documentation. The data analysis technique used in this research is multiple linear regression analysis using the SPSS version 25 program. Based on the results of the analysis, this research shows that transformational leadership has a positive and significant effect on employee performance, which means that the more transformational leadership increases, the more performance at PT Mitra Krida Mandiri in Badung Regency increases. Work motivation has a positive and significant effect on employee performance, which means that the better the motivation, the performance at PT Mitra Krida Mandiri in Badung Regency increases. Self-efficacy has a positive and significant effect on employee performance, which means that the better the self-efficacy, the performance at PT Mitra Krida Mandiri in Badung Regency increases.